Yap1-2 Isoform Is the Primary Mediator in TGF-β1 Induced EMT in Pancreatic Cancer - Gao, Chao; Quan, Mei-Yu; Chen, Qian-Jie; Yang, Ruo; Wu, Yuanyuan; Liu, Jia-Yu; Lin, Zhong-Yuan; Li, Xue; Cai, Jue-Ting; Jiang, Tian-Fang; Xu, Le; Mossahebi-Mohammadi, Majid; et al. (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is the most aggressive human malignancy and intrinsically resistant to conventional therapies. YAP1, as a key downstream effector of the Hippo pathway, plays an important role in tumorigenesis including PDAC. Alternative mRNA splicing of YAP1 results in at least 8 protein isoforms, which are divided into two subgroups (YAP1-1 and YAP1-2) based on the presence of either a single or double WW domains. We investigated the functions and regulatory mechanisms of YAP1-1 and YAP1-2 in PDAC cells induced by TGF-β to undergo epithelial-to-mesenchymal transition (EMT). CRISPR-Cas9 and shRNA were used to silence YAP1 expression in pancreatic cancer cells. Re-constituted lentivirus mediated overexpression of each single YAP1 isoform was generated in the parental knockout L3.6 cells. EMT was induced by treatment with TGF-β, EGF and bFGF in parental and the constructed stable cell lines. Western blot and qPCR were used to detect the expression of EMT markers. Scratch wound healing and transwell assays were used to detect cell migration. The stability and subcellular localization of YAP1 proteins were determined by Western blot analysis, immunofluorescence, as well as ubiquitination assays. We showed that TGF-β, EGF and bFGF all significantly promoted EMT in PDAC cells, which was inhibited by knockdown of YAP1 expression. Interestingly, YAP1-1 stable cells exhibited a stronger migratory ability than YAP1-2 cells under normal culture condition. However, upon TGF-β treatment, L3.6-YAP1-2 cells exhibited a stronger migratory ability than L3.6-YAP1-1 cells. Mechanistically, TGF-β treatment preferentially stabilizes YAP1-2 and enhances its nuclear localization. Furthermore, TGF-β-induced EMT and YAP1-2 activity were both blocked by inhibition of AKT signaling. Our results showed that both YAP1-1 and YAP1-2 isoforms are important mediators in the EMT process of pancreatic cancer. However, YAP1-2 is more important in mediating TGF-β-induced EMT, which requires AKT signaling.